Defective UiO‐66 toward boosted electrochemical nitrogen reduction to ammonia. (20th March 2022) - He, Xiaobo; Liao, Yuanxiu; Tan, Jiabin; Li, Guoru; Yin, Fengxiang
Highlights: Defective UiO-66-HAc is prepared by using acetic acid as defect modulator. More linkers are lost in UiO-66-HAc as compared with UiO-66 without using modulators. Abundant lost-linker defects bring UiO-66-HAc favorable structures for NRR. High Faradaic efficiency and high NH3 yield rate has been realized for NRR. Abstract: Electrochemical nitrogen reduction reaction (NRR) to ammonia is considered as one of the most promising green techniques, which is an alternative to traditional Haber-Bosch method. However, ammonia yield rate and Faradic efficiency is still limited currently, and thus efficient catalysts are still highly required. Herein, defective UiO-66 has been developed as highly active NRR catalyst by using acetic acid (HAc) or formic acid (FA) as defect modulators. Both the resultant defective UiO-66-HAc and UiO-66-FA include truncated cubic nanoparticles with the smaller sizes as compared with UiO-66 without acid modulator that consists of the larger sized octahedral nanoparticles. More importantly, both of them have more defects than UiO-66, which involve losing terephthalic linkers. The more linker-lost defects can expose the more Zr6 nodes as active sites, increase electrochemical specific surface areas, improve the adsorption strength of N2 and the N-related intermediates during NRR to NH3, enlarge the specific surface areas and pore volumes (or porosity) and thus increase the amounts of adsorbed N2 . As a result, the defective UiO-66-HAc with the most abundant lost linkers (or exposed Zr6 nodes) achieves the optimal catalytic performance of NRR to NH3 . This work fully shows that the defective metal-organic frameworks are promising catalysts for NRR to NH3 . Graphitical abstract: Defective UiO-66 modulated by acetic acid achieves the greatly boosted activity of NRR to NH3 due to the favorable structural features toward activity that benefit from abundant linker-lost defects. Image, graphical abstract